Genetic variants in the LAMA5 gene in pediatric nephrotic syndrome. - Braun, Daniela A; Warejko, Jillian K; Ashraf, Shazia; Tan, Weizhen; Daga, Ankana; Schneider, Ronen; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; Majmundar, Amar J; Nakayama, Makiko; Schapiro, David; et al. (Nephrol Dial Transplant, 2019)
BACKGROUND: Nephrotic syndrome (NS), a chronic kidney disease, is characterized by significant loss of protein in the urine causing hypoalbuminemia and edema. In general, ∼15% of childhood-onset cases do not respond to steroid therapy and are classified as steroid-resistant NS (SRNS). In ∼30% of cases with SRNS, a causative mutation can be detected in one of 44 monogenic SRNS genes. The gene LAMA5 encodes laminin-α5, an essential component of the glomerular basement membrane. Mice with a hypomorphic mutation in the orthologous gene Lama5 develop proteinuria and hematuria. METHODS: To identify additional monogenic causes of NS, we performed whole exome sequencing in 300 families with pediatric NS. In consanguineous families we applied homozygosity mapping to identify genomic candidate loci for the underlying recessive mutation. RESULTS: In three families, in whom mutations in known NS genes were excluded, but in whom a recessive, monogenic cause of NS was strongly suspected based on pedigree information, we identified homozygous variants of unknown significance (VUS) in the gene LAMA5. While all affected individuals had nonsyndromic NS with an early onset of disease, their clinical outcome and response to immunosuppressive therapy differed notably. CONCLUSION: We here identify recessive VUS in the gene LAMA5 in patients with partially treatment-responsive NS. More data will be needed to determine the impact of these VUS in disease management. However, familial occurrence of disease, data from genetic mapping and a mouse model that recapitulates the NS phenotypes suggest that these genetic variants may be inherited factors that contribute to the development of NS in pediatric patients.

Whole Exome Sequencing of Patients with Steroid-Resistant Nephrotic Syndrome. - Warejko, Jillian K; Tan, Weizhen; Daga, Ankana; Schapiro, David; Lawson, Jennifer A; Shril, Shirlee; Lovric, Svjetlana; Ashraf, Shazia; Rao, Jia; Hermle, Tobias; Jobst-Schwan, Tilman; Widmeier, Eugen; et al. (Clin J Am Soc Nephrol, 2018)
BACKGROUND AND OBJECTIVES: Steroid-resistant nephrotic syndrome overwhelmingly progresses to ESRD. More than 30 monogenic genes have been identified to cause steroid-resistant nephrotic syndrome. We previously detected causative mutations using targeted panel sequencing in 30% of patients with steroid-resistant nephrotic syndrome. Panel sequencing has a number of limitations when compared with whole exome sequencing. We employed whole exome sequencing to detect monogenic causes of steroid-resistant nephrotic syndrome in an international cohort of 300 families. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Three hundred thirty-five individuals with steroid-resistant nephrotic syndrome from 300 families were recruited from April of 1998 to June of 2016. Age of onset was restricted to <25 years of age. Exome data were evaluated for 33 known monogenic steroid-resistant nephrotic syndrome genes. RESULTS: In 74 of 300 families (25%), we identified a causative mutation in one of 20 genes known to cause steroid-resistant nephrotic syndrome. In 11 families (3.7%), we detected a mutation in a gene that causes a phenocopy of steroid-resistant nephrotic syndrome. This is consistent with our previously published identification of mutations using a panel approach. We detected a causative mutation in a known steroid-resistant nephrotic syndrome gene in 38% of consanguineous families and in 13% of nonconsanguineous families, and 48% of children with congenital nephrotic syndrome. A total of 68 different mutations were detected in 20 of 33 steroid-resistant nephrotic syndrome genes. Fifteen of these mutations were novel. , , , and were the most common genes in which we detected a mutation. In another 28% of families, we detected mutations in one or more candidate genes for steroid-resistant nephrotic syndrome. CONCLUSIONS: Whole exome sequencing is a sensitive approach toward diagnosis of monogenic causes of steroid-resistant nephrotic syndrome. A molecular genetic diagnosis of steroid-resistant nephrotic syndrome may have important consequences for the management of treatment and kidney transplantation in steroid-resistant nephrotic syndrome.